Human resource management and technology vol 2 - Saleh, Hasan (Penerbit UTeM Press, 2025)
This module discusses the development of competitive edge through effective applications of best Human Resources Management & technology practices by providing students with a broad overview of Human Resources Management (HRM) in the talent acquisition (staffing, recruitment and selection) and retention, Human Resource planning, training and development, performance appraisal, compensation, career management and safety of employees. Students are also provided with the understanding of Employment Laws by knowing the rights and obligations of employers and employees. Students will be exposed to key Human Resource Management and Technology issues, the use of e-Human Resource in transforming Human Resource service delivery using web-based technology and Human Resource Information System (HRIS) in transforming the firm's Human Resource practices and its Human Resource brand. The course also examines the trends in Human Resource technology and its impact resulting from the growth of social networking, compliance and reporting requirements. Simulations, business games and presentation sessions directly related to Human Resources Management and technology will be assimilated to enhance students' understanding of the course.